DEVELOPMENT DYNAMICS OF PESTS IN THE ALFALFA BIOTOPE, MEASURES TO CONTROL THE DOMINANT SPECIES - Тoreniyazov Elmurat Sherniyazovich,; Khamidullaev Janabergen Ubbiniyazovich, (EPRA International Journal of Research and Development (IJRD), 2022)
As a result of research, it was observed that phytonutrients, alfalfa saplings, alfalfa sap, alfalfa seeds, along with rodents and locusts, which are specialized in alfalfa fields, cause great damage to plants. The distribution areas of these pests during the growing season, the dynamics of development, the degree of damage were studied and control measures were developed.